Design-Based Stereology of the Lung in the Hyperoxic Preterm Rabbit Model of Bronchopulmonary Dysplasia. (6th October 2021) - Mühlfeld, Christian; Schulte, Henri; Jansing, Johanna Christine; Casiraghi, Costanza; Ricci, Francesca; Catozzi, Chiara; Ochs, Matthias; Salomone, Fabrizio; Brandenberger, Christina
Abstract : Bronchopulmonary dysplasia (BPD) is a complex condition frequently occurring in preterm newborns, and different animal models are currently used to mimic the pathophysiology of BPD. The comparability of animal models depends on the availability of quantitative data obtained by minimally biased methods. Therefore, the aim of this study was to provide the first design-based stereological analysis of the lungs in the hyperoxia-based model of BPD in the preterm rabbit. Rabbit pups were obtained on gestation day 28 (three days before term) by cesarean section and exposed to normoxic (21% O2, n = 8 ) or hyperoxic (95% O2, n = 8 ) conditions. After seven days of exposure, lung function testing was performed, and lungs were taken for stereological analysis. In addition, the ratio between pulmonary arterial acceleration and ejection time (PAAT/PAET) was measured. Inspiratory capacity and static compliance were reduced whereas tissue elastance and resistance were increased in hyperoxic animals compared with normoxic controls. Hyperoxic animals showed signs of pulmonary hypertension indicated by the decreased PAAT/PAET ratio. In hyperoxic animals, the number of alveoli and the alveolar surface area were reduced by one-third or by approximately 50% of control values, respectively. However, neither the mean linear intercept length nor the mean alveolar volume was significantly different between both groups. Hyperoxic pups had thickened alveolar septa and intra-alveolar accumulation of edema fluid and inflammatory cells. Nonparenchymal blood vessels had thickened walls, enlarged perivascular space, and smaller lumen in hyperoxic rabbits in comparison with normoxic ones. In conclusion, the findings are in line with the pathological features of human BPD. The stereological data may serve as a reference to compare this model with BPD models in other species or future therapeutic interventions.